Genetic aspects of criteria of trypanotolerance - Trail, J.C.M.; D'Ieteren, G.D.M.; Feron, A.; Itty, P.; Kakiese, O.; Maehl, J.H.H.; Mulungo, M.; Nagda, S.M.; Paling, R.W.; Pelo, M.; Rarieya, J.M.; Thorpe, W.R. (ILCA/ILRAD, 1988)
Discusses the genetic aspects of criteria of trypanotolerance including parasitaemia, anaemia control and immune response. Includes data on heritability estimates for daily liveweight change, for PCV under low & high trypanosome prevalence, and for number of treatments required in four periods after parturition.